Relevance of the intestinal health-related pathways to broiler residual feed intake revealed by duodenal transcriptome profiling. (18th November 2018) - Liu, Ranran; Liu, Jie; Zhao, Guiping; Li, Wei; Zheng, Maiqing; Wang, Jie; Li, Qinghe; Cui, Huanxian; Wen, Jie
ABSTRACT: In broiler production, there is a continuous effort to breed feed efficient chickens. Residual feed intake (RFI) is an accurate indicator that has been accepted as an alternative measure of the conventional feed conversion ratio. This study conducted a duodenal transcriptome survey to explore the molecular basis of broiler RFI. Results showed that there are 599 genes that were differentially expressed (DE) in the duodenum between high RFI and low RFI (LRFI) broilers. Functional analysis showed that RFI can be explained by differences in the regulation of the immune system process, complement activation, nutrient digestion, and absorption pathways. Among those processes, the glutathione S-transferase family and serpin family are involved in glutathione metabolism and TGF-β signaling. These genes are involved in complement and coagulation cascade pathways that constitute a new regulatory network to reduce oxidative stress and inflammatory reaction, as well as to improve the defense capability in LRFI broilers. Ten DE genes related to the digestive tract health and digestive function, CCK, MPEG1, EPHB2, SERPINH1, VANGL2, CYFIP2, PCDH19, TGFBI, SCUBE3 and CATHL1, were identified as candidate genes related to RFI. In conclusion, the results indicate that there is less oxidative stress, less inflammatory reactions, and better digestion and absorption in the duodenum of the LRFI broilers, which might result in improved intestinal health and contribute to an increase in the efficiency of feed conversion.